A repetitive deoxyribonucleic acid sequence that distinguishes Trypanosoma simiae from T. congolense - Majiwa, Phelix A.O.; Webster, P. (Cambridge University Press, 1987)
The dominant repetitive deoxyribonucleic acid (DNA) sequence in the genome of a clone ofTrypanosoma(Nannomonas)simiaehas been identified and cloned as a recombinant plasmid. The recombinant plasmid was used in hybridization analyses of DNA samples obtained from various trypanosome species and subspecies. The results indicated that theT. simiaerepetitive DNA sequence hybridized with DNA derived only fromT. simiae; it did not hybridize with DNA derived from clones or stocks ofT. congolense, or from any other trypanosome species examined. A preliminary characterization of the cloned DNA sequence and its use in the identification ofT. simiaeof similar genotypes are presented.